(untitled) (Interdisciplinary Studies Journal, 2025)
Since ancient times, the man has understood himself as a rational being and has considered nature and its resources as a means to achieve his well-being. However, over the centuries, this scenario has become a serious aggravating factor, since the excessive use of natural resources results in various environmental damages, bringing to light the destruction of the environment and thus accumulating harmful effects on his behavior. The objective of this research was to investigate the historical evolution of environmental licensing, as well as to identify the legal instruments and access to information on the websites of the environmental agencies of the Union and Amazonas. The research is qualitative, exploratory and a case study. In Brazil, there is extensive legislation aimed at environmental protection. A well-conducted and transparent environmental licensing procedure is beneficial to the environment, entrepreneurship and allows the integration between sustainable development and environmental preservation. All information related to environmental licensing is available to users on the websites of the environmental agencies of the Union and Amazonas.